USE AND AWARENESS OF DIGITAL RESOURCES AND SERVICES BY THE STUDENTS OF SELECTED ENGINEERING COLLEGES IN NAGPUR CITY, MAHARASHTRA - Dhepe, Pratik; Kharole, Dipak; Gabhane, Dhananjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the awareness and utilization of digital resources and services among students at four engineering colleges in Nagpur, Maharashtra: Tulsiram Gaikwad Patil College of Engineering and Technology, Wainganga College of Engineering and Management, Guru Nanak Institute of Engineering & Technology, and Nagarjuna Institute of Engineering Technology & Management. Data was gathered from 371 out of 500 students using a standardized questionnaire, resulting in an 71.2% response rate. The findings show that 61.2% of students are computer literate, with audio-video (58.5%) and graphics (56.6%) being the most familiar digital resources and CD-ROM/DVD (28.6%) being the least familiar. Students extensively rely on self-study (76.3%) and self-help guides (62.8%) for learning and support, and they predominantly use digital resources for job development (59.8%) and knowledge upgrading (60.5%). The results point to the need for improved infrastructure, training, and awareness campaigns by exposing gaps in advanced skills, institutional access, and structured help. This study emphasises how crucial it is to address gaps in digital literacy in order to maximise learning outcomes in engineering education.